Acetate Activation in Methanosaeta thermophila: Characterization of the Key Enzymes Pyrophosphatase and Acetyl-CoA Synthetase. (15th August 2012) - Berger, Stefanie; Welte, Cornelia; Deppenmeier, Uwe
Abstract : The thermophilic methanogen Methanosaeta thermophila uses acetate as sole substrate for methanogenesis. It was proposed that the acetate activation reaction that is needed to feed acetate into the methanogenic pathway requires the hydrolysis of two ATP, whereas the acetate activation reaction in Methanosarcina sp. is known to require only one ATP. As these organisms live at the thermodynamic limit that sustains life, the acetate activation reaction in Mt. thermophila seems too costly and was thus reevaluated. It was found that of the putative acetate activation enzymes one gene encoding an AMP-forming acetyl-CoA synthetase was highly expressed. The corresponding enzyme was purified and characterized in detail. It catalyzed the ATP-dependent formation of acetyl-CoA, AMP, and pyrophosphate( PP i ) and was only moderately inhibited byPP i . The breakdown ofPP i was performed by a soluble pyrophosphatase. This enzyme was also purified and characterized. The pyrophosphatase hydrolyzed the major part ofPP i (K M = 0.27 ± 0.05 mM) that was produced in the acetate activation reaction. Activity was not inhibited by nucleotides orPP i . However, it cannot be excluded that otherPP i -dependent enzymes take advantage of the remainingPP i and contribute to the energy balance of the cell.